ANALISIS BUKU AJAR BAHASA ARAB SEMESTER GANJIL KELAS II MADRASAH IBTIDAIYAH TERBITAN KEMENTRIAN AGAMA REPUBLIK INDONESIA - Yakin, Ainul; Rohman, Azizur (Universitas Al-Amien Prenduan, 2020)
Textbooks are very important in the teaching and learning process. Where in it includes the materials that will be discussed according to the level. Although it is difficult to get a perfect textbook in its design, it is very necessary to have a good textbook that suits the conditions of students. Therefore, the textbooks used need to be analyzed, whether they meet the criteria as a decent book or not. The focus of this study is an analysis of the suitability of the material in the Arabic Language Textbook Class II Madrasah Ibtidaiyah published by the Ministry of Religion of the Republic of Indonesia in 2020 with Basic competencies (KD) and the suitability of its language use with the age of grade II students of Madrasah Ibtidaiyah. In this study, the author used a qualitative study approach with the type of research being the analysis of tech books. The source of the research data uses a personal document, namely the Odd Semester Arabic textbook published by the Ministry of Religion of the Republic of Indonesia in 2020 Class II Madrasah Ibtidaiyah. The data analysis technique is a way to collect data in textbooks to analyze their suitability. The results of the study concluded that the suitability of the material in the Arabic Language Textbook Class II Madrasah Ibtidaiyah Published by the Ministry of Religion of the Republic of Indonesia in 2020 with KD has adjusted to KMA Number 183 of 2019 in the PAI and Arabic curriculum in Madrasah. Where the material contains a set of knowledge or information that can be accounted for scientifically and presented with a certain pattern of reasoning, as is the pattern of scientific reasoning (inductive, deductive, or mixed). Meanwhile, the suitability of language with the age of grade II students of Madrasah Ibtidaiyah is in accordance with the level of intellectual, social, and emotional development of early students of madrasah ibtidaiyah. No language, words, or sentences were found that were foreign and that did not match the age of the MI child. and the language used also does not make it difficult for students to read sentences in the reading or text, many sentences are in the form of effective sentences.